Dakwah Islam Pesisir: Kajian Metode Dakwah - Abd. Kholiq, Abd. Kholiq (ALAMTARA, 2024)
Islam in the archipelago has had a long history on the coast, areas located on the coast and which were trade centers or major ports in the past. The coast is often a meeting point between various cultures, religions and civilizations, thus playing an important role in the spread and development of Islam in the region. Islam has spread widely in coastal areas through various different routes. The spread and development of Islam on the coast was influenced by several factors. As explained in various Islamic historical literature, there are several routes used by the carriers of Islam to spread Islam in the archipelago. On the other hand, Islamic boarding schools are materially a continuation of the Islamic mission, there are charismatic figures who are role models and role models. In this way, society will obtain prosperity and its true meaning. And on the other hand, it seems that Islamic boarding schools will have a huge meaning for society if all of this can really be realized, or in other words, that the burden borne by Islamic boarding schools is not small to be able to fulfill their role in society. Islamic Da'wah must not stop in the system of implementing da'wah. So what needs to be prepared in the relay for implementing da'wah is the establishment of an Islamic educational institution in the form of a boarding school as the forerunner of an Islamic educational institution.